The merry matchmaker [large type] - Roberts, Sheila, 1951- (Thorndike Press large print romance series., 2024)
Frankie Lane knows what's best for just about everyone. Her divorced sister, Stef; her shy employee, Elinor; her daughter, Natalie, who really needs to start her own business selling the chocolates she makes at home; even her best friend, Viola, who is trying to renovate her old Victorian; then there's Mitch Howard, the owner of the local hardware store. They've been friends ever since Frankie opened her store nine years earlier. He's been divorce for years and it's such a waste of a man! Mitch is the finest man Frankie knows. He's easygoing, wise, and kindhearted. Mitch needs someone, and she's determined to help him find that someone, whether he likes it or not. Inspired by Jane Austen's Emma.